The international law of maritime boundaries and the practice of states in the Mediterranean Sea - Ahnish, Faroj Abdullah (Oxford : Clarendon Press, 1993)
A revised and updated Ph.D. theses submitted in 1989 to the University of Cambridge.
Keywords: Baselines (Maritime law).; Baselines (Maritime law) -- Mediterranean Region; Continental shelf -- Mediterranean Region; ontinental shelf; Territorial waters; Territorial waters -- Mediterranean Region